KAJIAN STILISTIKA DAN STRUKTUR CERPEN “TAK ADA YANG GILA DI KOTA INI” KARYA EKA KURNIAWAN - Ajeng Hadyian; Dipa Septya Nugraha; Siti Mawaddatul Fitriyyah (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2022)
This research was conducted to examine a short story entitled "Nothing is crazy in this city" by Eka Kurniawan in an anthology of short stories entitled Love is not dead. In this short story study contains two study materials in it, namely the study of stylistics and structure in the short story "Nothing is crazy in this city". The stylistic study referred to according to Tuloli in Lafamane (2020) stylistics or stylistics in general talks about the use of a distinctive or special language, which is the hallmark of a writer, literary school, or also deviations from everyday language or from normal or normal language. standard, and so on. In this study, the short story contains aspects of the provisions of stylistic studies, such as sound style, sentence style, discourse slot gacor, figurative language and imagery. Then the short story has the stages of the short story as a coherent structure, including: Abstraction, orientation, complication, evaluation, resolution and code.